Female Offenders' Multiple Goals for Engaging in Desired Communication with Their Probation/Parole Officers. Issue 1 (1st January 2017) - Cornacchione, Jennifer; Smith, Sandi W.
Abstract : The multiple goals approach is used to assess whether or not women on probation or parole engaged in communication with their probation/parole officers (PO) regarding needs or issues they had and about which they wanted to talk. Interviews were conducted with 402 women on probation and parole across Michigan; 127 stated that there was a time when they wanted to talk to their PO about a difficult need or issue they were facing, including housing and illegal activity. Women who were concerned about threats to their freedom were less likely to have initiated the conversation. Findings highlight possible reasons that impact whether or not individuals engage in difficult conversations that are desired.